Pemanfaatan Aplikasi Digital sebagai Alat Bantu Diagnosa Status Gizi dan Deteksi Dini Stunting - Rikwan; Ni Ketut Marlina; Arpin Arpin; Matius Paundanan; Lexy Kareba; Athia Kurnia Kasim; Sri Multi; Nurwahidah (LPPM Universitas Widya Nusantara, 2025)
Good nutrition is crucial during the first 1,000 days of life, influencing a child’s physical and cognitive development. In Indonesia, malnutrition—particularly stunting—poses a significant public health problem, with 21.6% of children under five affected in 2022. Stunting leads to long-term consequences such as learning difficulties and reduced productivity, requiring a cross-sectoral approach that involves improving maternal nutrition and healthcare services. This community service program aims to enhance the awareness and skills of parents and healthcare workers in utilizing digital technology for the early detection of nutritional status and stunting risk. The activity employed a quantitative–descriptive design through training sessions, direct observation, and nutritional status assessments conducted before and after the intervention. A total of 31 children under five were evaluated using anthropometric indicators such as weight-for-age (W/A), height-for-age (H/A), and weight-for-height (W/H). The intervention involved training and the implementation of a digital application, which significantly improved the efficiency of data collection and analysis. Findings indicated a 90% improvement in cadres’ digital recording competencies and a reduction in data entry errors from 15% to 2%. Most children demonstrated good nutritional status (67.75%), while 35.48% were classified as mildly stunted and 3.22% as severely stunted. The program’s impact included enhanced data accuracy and increased parental awareness of child growth monitoring. Challenges encountered during implementation included limited internet connectivity and varying participants’ digital literacy. It is recommended that similar programs be conducted regularly with continued mentorship and technical support to ensure sustainability.